The Service Program of “You May Not Stop From School” as a Way of the Fulfillment of Educational Rights For Street Children and Dropouts in Palembang - Ahmad Zulinto; Muhammad Kristiawan; Rambat Nur Sasongko (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Based on statistical data from the Ministry of Education and Culture in 2018, the dropout rate in South Sumatra Province was very high. Especially for the Palembang City area, there were about 17% of the cases of children dropping out of school in South Sumatra until 2018. The large number of children who have dropped out of school and who were not in school cause exploited children to be still often found on the streets, joining their parents to earn a living and even vulnerable to being involved in various juvenile delinquency and other criminal acts. Based on this fact, the Palembang City Government (Pemkot) in 2019, through the Palembang City Education Office, then developed a program to eradicate school dropouts and street children called the